Mat Graduate Students' Experiences And Satisfaction With The Educational Services Of Omsc Graduate School - Casanova, Venessa S.; Luisa P. Pullido, Maria (CV. Inara, 2022)
This descriptive-correlational study determined the learning experiences and satisfaction of the Master of Arts in Teaching English and Filipino program graduates in Occidental Mindoro State College Graduate School.The study was conducted from January 2021 until August 2021 at OMSC Labangan Campus, San Jose, Occidental Mindoro. A total of 25 respondents selected through simple random sampling participated in the study. Self-made questionnaire was the main instrument used in gathering data for the study. Data gathered were analyzed using frequency and percentage, weighted mean, and Pearson-r moment correlation. The respondents are middle-aged females who took Master of Arts in Teaching English, a regular rank and file employees whose monthly income is Php 21,000-30,000. The extent of their learning experience is very high and with an overall high satisfaction level in terms of administrative support, faculty, curriculum, and student services. There is a relationship between profile, the extent of experience, and the level of satisfaction. Profile variables influence satisfaction. The provision of quality higher education services enhance graduate students' learning experience and can influence their level of satisfaction.